Analysis of Efficiency and Break Even Point of Sheep Farming at Sukawangi Village Sumedang Regency - Jelita, Anggia; Herlina, Linda; Firman, Achmad (Jurnal Peternakan, 2024)
This study analyzes efficiency and break even point to provide an overview of sheep farming in Sukawangi Village, Pamulihan Subdistrict, Sumedang Regency in July 2023. The aims of this study is to count total production cost, find out farmer’s income, and analyze the eficiency and break even point of sheep farming. The method used was a survey by interviewing 88 farmers using simple random sampling. Based on the results of the study, it showed that the total production costs for sheep farming in Sukawangi Village are IDR 27,432,069/unit enterprises/year, and the income is IDR 3,055,431/unit enterprises/year. The efficiency value of the sheep farming business in Sukawangi Village is 1.11 which means that the business is efficient and profitable. The production break event point value is 3 heads adult sheep equivalent, smaller than actual sales which is 6 heads  adult sheep equivalent, while the price break event value is IDR 4,238,845/unit enterprises/year, smaller than the actual sales price, which is IDR 4,710,975/unit enterprises/year.